Biodegradable zinc-based GBR film as well as preparation method and application thereof

A biodegradable zinc-based GBR membrane with a double-layer structure, prepared via zinc alloy and polymer mixing, melt extrusion, and 3D printing, offers improved mechanical strength and bone regeneration, overcoming the limitations of traditional membranes.

CN119185645APending Publication Date: 2024-12-27BAISI BORUI MEDICAL TECH (SUZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411369415.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Current GBR membranes, particularly collagen membranes, lack mechanical strength, fail to maintain a bone formation space, and have no antibacterial effect, limiting their effectiveness in oral implantation and bone defect repair.

Method used

A biodegradable zinc-based GBR membrane is prepared by mixing a zinc alloy with a biodegradable polymer material, followed by melt extrusion and 3D printing, creating a double-layer structure with a porous polymer layer for cell penetration and a supporting zinc layer for mechanical strength, customizable to patient anatomy.

Benefits of technology

The biodegradable zinc-based GBR membrane provides enhanced mechanical properties, promotes bone tissue regeneration and vascularization, and exhibits good biocompatibility and biodegradability, addressing the limitations of traditional membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119185645A_ABST
    Figure CN119185645A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oral implantation and bone defect repair, and provides a biodegradable zinc-based GBR membrane as well as a preparation method and application thereof. The method comprises the following steps: mixing a zinc alloy, a biodegradable polymer material and a solvent to obtain a mixed solution; drying the mixed solution to obtain a composite membrane; performing first melt extrusion on the composite film to obtain first composite filaments; performing second melt extrusion on the first composite filaments to obtain second composite filaments; the second composite filaments are subjected to 3D printing, and the biodegradable zinc-based GBR film is obtained. According to the biodegradable zinc-based GBR membrane, the zinc alloy and the biodegradable high polymer material are compounded to form a membrane with a double-layer structure, and the biodegradable zinc-based GBR membrane not only has good biocompatibility and biodegradability, but also has the potential of promoting bone tissue regeneration and vascularization, so that the limitation of a traditional GBR membrane is effectively solved; and a new solution is provided for oral implantation and bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oral implantation and bone defect repair, and in particular to a biodegradable zinc-based GBR membrane and a preparation method and application thereof. Background Art

[0002] In the field of oral implants and bone defect repair, guided bone regeneration (GBR) technology is an important treatment method. The GBR membranes currently used mainly include two categories: biodegradable and non-degradable. Biodegradable barrier membranes mainly include animal-derived components (such as collagen membranes) and aliphatic polyesters (such as polylactic acid PLA). Non-degradable barrier membranes mainly include polytetrafluoroethylene (PTFE) membranes and titanium membranes. Among them, collagen membranes have excellent performance in GBR and are widely used, but they have poor strength, cannot maintain a good bone formation space, and have no antibacterial effect.

[0003] Therefore, it is of great significance to design and prepare a GBR membrane with excellent performance to further improve the treatment effect and bring better clinical experience to patients. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and provide a biodegradable zinc-based GBR membrane and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a biodegradable zinc-based GBR film, comprising the following steps:

[0007] (1) mixing a zinc alloy, a biodegradable polymer material and a solvent to obtain a mixed solution; drying the mixed solution to obtain a composite film;

[0008] (2) subjecting the composite film to a first melt extrusion to obtain a first composite filament; subjecting the first composite filament to a second melt extrusion to obtain a second composite filament;

[0009] (3) 3D printing the second composite filament to obtain the biodegradable zinc-based GBR membrane.

[0010] Preferably, the biodegradable polymer material in step (1) includes one or more of polylactic acid, polyglycolic acid and polylactic acid-glycolic acid copolymer; and the solvent includes one or more of dichloromethane, acetone and ethyl acetate.

[0011] Preferably, the molecular weight of the polylactic acid is 5*10 4 ~2*10 5 g / mol, the molecular weight of polyglycolic acid is 3*104 ~1*10 5 g / mol, the molecular weight of polylactic acid-co-glycolic acid is 1*10 4 ~5*10 4 g / mol, and the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 50-85:15-50.

[0012] Preferably, in step (1), the mass volume ratio of the zinc alloy, the biodegradable polymer material and the solvent is 1-2 g: 2-4 g: 10-12 mL.

[0013] Preferably, the drying temperature in step (1) is 40-60°C.

[0014] Preferably, in step (2), the temperature of the first melt extrusion is 175-185° C., the nozzle diameter of the first melt extrusion is 0.15-0.25 mm, and the extrusion speed of the first melt extrusion is 50-60 mm / s.

[0015] Preferably, in step (2), the temperature of the second melt extrusion is 170-180° C., the nozzle diameter of the second melt extrusion is 0.15-0.25 mm, and the extrusion speed of the second melt extrusion is 40-50 mm / s.

[0016] Preferably, the printing temperature of the 3D printing in step (3) is 190-200° C., the printing layer thickness of the 3D printing is 0.1-0.3 mm, the printing speed of the 3D printing is 30-50 mm / s, and the machine temperature of the 3D printing is 40-60° C.

[0017] The present invention also provides a biodegradable zinc-based GBR film prepared by the preparation method of the biodegradable zinc-based GBR film.

[0018] The present invention also provides the use of the biodegradable zinc-based GBR membrane in preparing oral implant materials or bone defect repair materials.

[0019] The beneficial effects of the present invention are:

[0020] The present invention provides a method for preparing a biodegradable zinc-based GBR membrane, comprising the following steps: mixing a zinc alloy, a biodegradable polymer material and a solvent to obtain a mixed solution; drying the mixed solution to obtain a composite membrane; subjecting the composite membrane to a first melt extrusion to obtain a first composite filament; subjecting the first composite filament to a second melt extrusion to obtain a second composite filament; and 3D printing the second composite filament to obtain a biodegradable zinc-based GBR membrane. The present invention composites a zinc alloy with a biodegradable polymer material to form a membrane with a double-layer structure, wherein the biodegradable polymer material has the function of promoting cell growth and nutrient exchange, and the zinc alloy can provide the mechanical properties required for the GBR membrane. The present invention adopts 3D printing technology to prepare a biodegradable zinc-based GBR membrane, and realizes a customized design according to the oral CT data of the patient through 3D printing technology to adapt to the oral anatomical structure of different patients, which can greatly improve the fit and repair effect. In addition, the biodegradable zinc-based GBR membrane prepared by the present invention can also be safely degraded by the biological internal environment after completing the guided bone regeneration effect. The biodegradable zinc-based GBR membrane prepared by the present invention not only has good biocompatibility and biodegradability, but also has the potential to promote bone tissue regeneration and vascularization, effectively solving the limitations of traditional GBR membranes and providing a new solution for oral implantation and bone defect repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the structure of the biodegradable zinc-based GBR membrane of the present invention; Figure 1 In the figure, 1 is the polymer layer, and 2 is the zinc-based layer;

[0022] Figure 2 Schematic diagram of cell survival of the biodegradable zinc-based GBR membrane obtained in Examples 1-2. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing a biodegradable zinc-based GBR film, comprising the following steps:

[0024] (1) mixing a zinc alloy, a biodegradable polymer material and a solvent to obtain a mixed solution; drying the mixed solution to obtain a composite film;

[0025] (2) subjecting the composite film to a first melt extrusion to obtain a first composite filament; subjecting the first composite filament to a second melt extrusion to obtain a second composite filament;

[0026] (3) 3D printing the second composite filament to obtain the biodegradable zinc-based GBR membrane.

[0027] In the present invention, the zinc alloy in step (1) preferably contains zinc and other biocompatible metal elements, and the mass fraction of other biocompatible metal elements in the zinc alloy is preferably 0-10% but not including 0; more specifically, when the other biocompatible metal element is Cu, the mass fraction of Cu in the zinc alloy is preferably 0.5-5%, further preferably 1-4%, and more preferably 2-3%; when the other biocompatible metal element is Mn, the mass fraction of Mn in the zinc alloy is preferably 0.5-3%, further preferably 1-2.5%, and more preferably 1.5-2%; when the other biocompatible metal element is Mg, the mass fraction of Mg in the zinc alloy is preferably 1-10%, further preferably 2-8%, and more preferably 3-5%; when the other biocompatible metal element is a metal element other than Cu, Mn, and Mg, the mass fraction of the metal element in the zinc alloy is preferably 0-1% but not including 0, further preferably 0.2-0.8%, and more preferably 0.5-0.6%.

[0028] In the present invention, the biodegradable polymer material in step (1) preferably includes one or more of polylactic acid, polyglycolic acid and polylactic acid-glycolic acid copolymer; the biodegradable polymer material must comply with biocompatibility standards, such as ISO 10993 series standards, to ensure safety in the body; the solvent preferably includes one or more of dichloromethane, acetone and ethyl acetate.

[0029] In the present invention, the molecular weight of the polylactic acid (PLA) is preferably 5*10 4 ~2*10 5 g / mol, more preferably 7*10 4 ~1.5*10 5 g / mol, more preferably 8*10 4 ~9*10 4 g / mol; the molecular weight of polyglycolic acid (PGA) is 3*10 4 ~1*10 5 g / mol, more preferably 5*10 4 ~8*10 4 g / mol, more preferably 6*10 4 ~7*10 4 g / mol; polylactic acid or polyglycolic acid is set within the above-mentioned specific molecular weight range to ensure that polylactic acid or polyglycolic acid has good processing properties and mechanical strength, and the specific molecular weight value is determined by conventional technical means in the field according to application requirements; polylactic acid or polyglycolic acid is preferably purchased from Dongguan Dihua Engineering Plastics Co., Ltd., Natureworks or Sigma-Aldrich.

[0030] In the present invention, the molecular weight of polylactic acid-co-glycolic acid (PLGA) is preferably 1*10 4 ~5*10 4 g / mol, more preferably 2*10 4 ~4*10 4 g / mol, more preferably 3*10 4 g / mol; the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is preferably 50-85:15-50, further preferably 55-80:20-45, and more preferably 75:25; the ratio of lactic acid to glycolic acid is set within the above range to ensure that the polylactic acid-glycolic acid copolymer has good biocompatibility and biodegradability; PLGA is preferably purchased from Sigma-Aldrich or Corbion.

[0031] In the present invention, the mass volume ratio of the zinc alloy, biodegradable polymer material and solvent in step (1) is preferably 1-2 g: 2-4 g: 10-12 mL, more preferably 1.2-1.8 g: 2.5-3.5 g: 10.5-11.5 mL, and more preferably 1.5 g: 3 g: 11 mL.

[0032] In the present invention, in step (1), a composite film is prepared by a solvent evaporation method, and step (1) specifically comprises the following steps: mixing a biodegradable polymer material with a solvent, dissolving the biodegradable polymer material completely under stirring conditions, then adding a zinc alloy, stirring evenly, and then performing ultrasonic treatment to further improve the dispersibility of the zinc alloy and the polymer material to obtain a mixed solution; pouring the mixed solution into a mold, placing it in a temperature-controlled oven for drying, evaporating the solvent, and forming a composite film; the ultrasonic treatment time is preferably 25 to 35 minutes, more preferably 27 to 33 minutes, and more preferably 30 minutes.

[0033] In the present invention, the drying temperature in step (1) is preferably 40 to 60°C, more preferably 45 to 55°C, and even more preferably 50°C.

[0034] In the present invention, the composite film prepared in step (1) is cut to obtain a first sample, and then the first sample is subjected to a first melt extrusion to obtain a first composite filament; the size of the first sample is preferably 2-3mm*2-3mm*2-3mm, further preferably 2.2-2.8mm*2.2-2.8mm*2.2-2.8mm, more preferably 2.5mm*2.5mm*2.5mm; setting the size of the first sample within the above range can ensure that during the extrusion process, the material can pass through the nozzle smoothly and maintain a good melt mixing effect; during the first melt extrusion, the cut first sample is placed in the hopper of the extruder to ensure that the hopper is filled with an appropriate amount to facilitate uniform feeding.

[0035] In the present invention, the temperature of the first melt extrusion in step (2) is preferably 175-185°C, more preferably 177-183°C, and more preferably 180°C; the nozzle diameter of the first melt extrusion is preferably 0.15-0.25 mm, more preferably 0.17-0.23 mm, and more preferably 0.20 mm; the extrusion speed of the first melt extrusion is preferably 50-60 mm / s, more preferably 52-58 mm / s, and more preferably 55-56 mm / s.

[0036] In the present invention, the first composite filament is cut to obtain a second sample, and then the second sample is subjected to a second melt extrusion to obtain a second composite filament; the purpose of the second melt extrusion is to ensure the uniformity and consistency of the distribution of zinc alloy particles; the length of the second sample is preferably 1 to 2 mm, more preferably 1.2 to 1.8 mm, and more preferably 1.5 mm.

[0037] In the present invention, the temperature of the second melt extrusion in step (2) is preferably 170-180°C, more preferably 172-178°C, and more preferably 175-176°C; the nozzle diameter of the second melt extrusion is preferably 0.15-0.25 mm, more preferably 0.17-0.23 mm, and more preferably 0.20 mm; the extrusion speed of the second melt extrusion is preferably 40-50 mm / s, more preferably 43-47 mm / s, and more preferably 45-46 mm / s.

[0038] In the present invention, in step (3), the second composite filament is placed in an industrial-grade FDM 3D printer, and is laid layer by layer along a predetermined path according to a CAD file to perform 3D printing to print out a biodegradable zinc-based GBR membrane that meets the requirements.

[0039] In the present invention, the printing temperature of the 3D printing in step (3) is preferably 190-200°C, more preferably 192-198°C, and more preferably 195°C; the printing layer thickness of 3D printing is preferably 0.1-0.3mm, more preferably 0.15-0.25mm, and more preferably 0.2mm; the printing speed of 3D printing is preferably 30-50mm / s, more preferably 35-45mm / s, and more preferably 40mm / s; the machine tool temperature of 3D printing is preferably 40-60°C, more preferably 45-55°C, and more preferably 50°C; setting the 3D printing conditions within the above range can optimize the physical properties and biocompatibility of the biodegradable zinc-based GBR membrane.

[0040] The present invention also provides a biodegradable zinc-based GBR film prepared by the preparation method of the biodegradable zinc-based GBR film.

[0041] The schematic diagram of the structure of the biodegradable zinc-based GBR membrane in the present invention is as follows: Figure 1 As shown; Figure 1 In the figure, 1 is a polymer layer and 2 is a zinc-based layer. Figure 1 As can be seen in the figure, the biodegradable zinc-based GBR membrane has a double-layer structure. The upper layer is a porous structure that is conducive to cell penetration and nutrient exchange; the lower layer is a supporting structure that provides the necessary mechanical strength. This structural design helps to address the limitations of traditional GBR membranes while promoting bone tissue regeneration and vascularization.

[0042] The present invention also provides the use of the biodegradable zinc-based GBR membrane in preparing oral implant materials or bone defect repair materials.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] The zinc alloy in this embodiment contains zinc and copper elements, and the mass fraction of Cu is 3%;

[0046] Poly(lactic acid-co-glycolic acid) (PLGA, PLGA molecular weight is 5*10 4g / mol, the molar ratio of lactic acid to glycolic acid in PLGA is 75:25, purchased from Sigma-Aldrich) is mixed with dichloromethane, and PLGA is completely dissolved under stirring conditions, and then zinc alloy is added, wherein the mass volume ratio of zinc alloy, PLGA and dichloromethane is 1g:2g:10mL, stirred evenly, and then ultrasonically treated for 30min to obtain a mixed solution; the mixed solution is poured into a mold, the thickness is set to 2.5mm, and finally placed in a temperature-controlled oven at 40°C for drying to evaporate the solvent to form a composite film;

[0047] The composite film was cut to obtain a first sample with a size of 2 mm*2 mm*2 mm, which was put into a hopper of an extruder, and extruded through a nozzle with a diameter of 0.2 mm at 180° C., and the extrusion speed was set to 50 mm / s to obtain a first composite filament; the first composite filament was cut to obtain a second sample with a length of 1.5 mm, which was extruded through a nozzle with a diameter of 0.2 mm at 175° C., and the extrusion speed was set to 45 mm / s to obtain a second composite filament;

[0048] An industrial-grade FDM 3D printer was used, with the printing temperature set to 190°C, the printing layer thickness to 0.2mm, the printing speed to 40mm / s, and the machine temperature to 50°C. According to the CAD design file, the membrane was laid layer by layer along the predetermined path for 3D printing to print out a biodegradable zinc-based GBR membrane that adapts to the patient's oral anatomical structure.

[0049] According to ASTM D7264-2015, the biodegradable zinc-based GBR membrane prepared in this embodiment was subjected to a mechanical property test, and the flexural strength of the GBR membrane obtained in this embodiment reached 50 MPa, which meets the mechanical requirements of oral implantation and bone defect repair.

[0050] Example 2

[0051] The zinc alloy of this embodiment contains zinc and magnesium elements, and the mass fraction of Mg is 1%;

[0052] Polylactic acid (PLA, the molecular weight of PLA is 1.5*10 5 g / mol, purchased from Natureworks) was mixed with dichloromethane, PLA was completely dissolved under stirring conditions, and then zinc alloy was added, wherein the mass volume ratio of zinc alloy, PLA and dichloromethane was 1g:3g:12mL, stirred evenly, and then ultrasonically treated for 30min to obtain a mixed solution; the mixed solution was poured into a mold with a thickness set to 2mm, and finally placed in a temperature-controlled oven at 40°C for drying to evaporate the solvent to form a composite film;

[0053] The composite film was cut to obtain a first sample with a size of 2 mm*2 mm*2 mm, which was put into a hopper of an extruder, and extruded through a nozzle with a diameter of 0.2 mm at 175° C., and the extrusion speed was set to 55 mm / s to obtain a first composite filament; the first composite filament was cut to obtain a second sample with a length of 1.5 mm, which was extruded through a nozzle with a diameter of 0.2 mm at 175° C., and the extrusion speed was set to 40 mm / s to obtain a second composite filament;

[0054] An industrial-grade FDM 3D printer was used, with the printing temperature set to 195°C, the printing layer thickness to 0.25mm, the printing speed to 35mm / s, and the machine temperature to 55°C. According to the CAD design file, the membrane was laid layer by layer along the predetermined path for 3D printing to print out a biodegradable zinc-based GBR membrane that adapts to the patient's oral anatomical structure.

[0055] According to ASTM D638, the biodegradable zinc-based GBR membrane prepared in this embodiment was subjected to a mechanical property test, and the tensile strength of the GBR membrane obtained in this embodiment reached 45 MPa, and the elongation at break was 15%, indicating good mechanical support capability.

[0056] According to ISO 10993-12:2021, IDT, the biocompatibility of the biodegradable zinc-based GBR membrane prepared in Examples 1 to 2 was tested, and a schematic diagram of cell survival of the biodegradable zinc-based GBR membrane obtained in Examples 1 to 2 was obtained, as shown in FIG. Figure 2 shown; from Figure 2 It can be seen that the biodegradable zinc-based GBR membrane in Example 1 is non-toxic to osteoblasts and fibroblasts, and the cell survival rate is over 95%; the biodegradable zinc-based GBR membrane in Example 2 has a high cell survival rate after being cultured with osteoblasts for 24h and 48h, showing good activity and is suitable for clinical application.

[0057] Comparative Example 1

[0058] Polylactic acid (PLA, the molecular weight of PLA is 1.5*10 5 g / mol, purchased from Natureworks) was mixed with dichloromethane, the mass volume ratio of PLA to dichloromethane was 1:20, and PLA was completely dissolved under stirring to obtain a mixed solution; the mixed solution was poured into a mold with a thickness set to 2 mm, and finally placed in a temperature-controlled oven at 40°C for drying to evaporate the solvent and form a PLA film.

[0059] According to ASTM D638, the PLA film prepared in this comparative example was subjected to a mechanical property test, and the tensile strength of the PLA film obtained in this comparative example was low, which was only about 25 MPa.

[0060] The PLA film obtained in the comparative example cannot be customized according to the patient's oral anatomical structure, while the biodegradable zinc-based GBR film obtained in Examples 1 to 2 can be customized through 3D printing technology to improve the fit and repair effect. In addition, the PLA film obtained in the comparative example did not show a significant antibacterial effect, while the biodegradable zinc-based GBR film obtained in Examples 1 to 2 showed good antibacterial properties due to the addition of zinc alloy, which helped to reduce the risk of infection.

[0061] It can be seen from the above embodiments that the present invention provides a method for preparing a biodegradable zinc-based GBR membrane, comprising the following steps: mixing a zinc alloy, a biodegradable polymer material and a solvent to obtain a mixed solution; drying the mixed solution to obtain a composite membrane; subjecting the composite membrane to a first melt extrusion to obtain a first composite filament; subjecting the first composite filament to a second melt extrusion to obtain a second composite filament; and 3D printing the second composite filament to obtain a biodegradable zinc-based GBR membrane. The present invention composites a zinc alloy with a biodegradable polymer material to form a membrane with a double-layer structure. The biodegradable polymer material has the function of promoting cell growth and nutrient exchange, and the zinc alloy can provide the mechanical properties required for the GBR membrane. The present invention uses 3D printing technology to prepare a biodegradable zinc-based GBR membrane, and uses 3D printing technology to achieve customized design according to the patient's oral CT data to adapt to the oral anatomical structure of different patients, which can greatly improve the fit and repair effect. In addition, the biodegradable zinc-based GBR membrane prepared by the present invention can also be safely degraded by the biological environment after completing the guided bone regeneration effect. The biodegradable zinc-based GBR membrane prepared by the present invention not only has good biocompatibility and biodegradability, but also has the potential to promote bone tissue regeneration and vascularization, effectively solving the limitations of traditional GBR membranes and providing a new solution for oral implantation and bone defect repair.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a biodegradable zinc-based GBR membrane, characterized in that: It includes the following steps: (1) mixing a zinc alloy, a biodegradable polymer material and a solvent to obtain a mixed solution; drying the mixed solution to obtain a composite film; (2) subjecting the composite film to a first melt extrusion to obtain a first composite filament; subjecting the first composite filament to a second melt extrusion to obtain a second composite filament; (3) 3D printing the second composite filament to obtain the biodegradable zinc-based GBR membrane.

2. The method for preparing the biodegradable zinc-based GBR membrane according to claim 1, characterized in that: The biodegradable polymer material in step (1) includes one or more of polylactic acid, polyglycolic acid and polylactic acid-glycolic acid copolymer; the solvent includes one or more of dichloromethane, acetone and ethyl acetate.

3. The method for preparing the biodegradable zinc-based GBR membrane according to claim 2, characterized in that: The molecular weight of the polylactic acid is 5*10 4 ~2*10 5 g / mol, the molecular weight of polyglycolic acid is 3*10 4 ~1*10 5 g / mol, the molecular weight of polylactic acid-co-glycolic acid is 1*10 4 ~5*10 4 g / mol, and the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 50-85:15-50.

4. The method for preparing a biodegradable zinc-based GBR membrane according to claim 2 or 3, characterized in that: The mass volume ratio of the zinc alloy, biodegradable polymer material and solvent in step (1) is 1-2 g: 2-4 g: 10-12 mL.

5. The method for preparing the biodegradable zinc-based GBR membrane according to claim 4, characterized in that: The drying temperature in step (1) is 40-60°C.

6. The method for preparing the biodegradable zinc-based GBR membrane according to claim 5, characterized in that: In step (2), the temperature of the first melt extrusion is 175-185° C., the nozzle diameter of the first melt extrusion is 0.15-0.25 mm, and the extrusion speed of the first melt extrusion is 50-60 mm / s.

7. The method for preparing the biodegradable zinc-based GBR membrane according to claim 1 or 6, characterized in that: In step (2), the temperature of the second melt extrusion is 170-180° C., the nozzle diameter of the second melt extrusion is 0.15-0.25 mm, and the extrusion speed of the second melt extrusion is 40-50 mm / s.

8. The method for preparing the biodegradable zinc-based GBR membrane according to claim 7, characterized in that: The printing temperature of the 3D printing in step (3) is 190-200° C., the printing layer thickness of the 3D printing is 0.1-0.3 mm, the printing speed of the 3D printing is 30-50 mm / s, and the machine temperature of the 3D printing is 40-60° C.

9. The biodegradable zinc-based GBR membrane prepared by the method for preparing a biodegradable zinc-based GBR membrane according to any one of claims 1 to 8.

10. Use of the biodegradable zinc-based GBR membrane according to claim 9 in the preparation of oral implant materials or bone defect repair materials.

Citation Information

Cited By

  • Preparation method and application of gelatin / sodium alginate / mesoporous bioactive glass composite guided bone tissue regeneration membrane

    CN121003735A